Imperial Ideology Expressed in the Church Architecture of the Tsar Dusan the Mighty and His Nobles in Macedonia - Nemykina, Elena A. (Actual Problems of Theory and History of Art, 2021)
The article is devoted to the peculiarities of iconographic programs of the fresco cycles during the reign of Stefan Dusan the Mighty, formed under the influence of the political ideology and imperial ambitions of the Serbian ruler. The annexation of new territories, strengthening of the political ambitions of the Serbian state, and desire of the strongest king in history of Serbia, Stephen Dusan, who declared himself a tsar in 1346, to see his country on an equal footing with the Byzantine Empire, the Serbian Autocephalous Church with the Patriarchate of Constantinople, and himself equal with the Byzantine Basileus, brings to the fore the imperial problematic for the art of the entire region. The analysis of the Macedonian fresco ensembles of this period is one of the crucial aspects for a deeper understanding of the evolution of medieval painting in Serbia and Macedonia at the stage when the territories with different historical, political, and ethnic constituents had been included in the Serbian state.This research has been completed with the support of the Russian Science Foundation (RSF), project № 20-18-00294.
Keywords: Serbia; Macedonia; medieval painting; Stefan Dusan; medieval art; imperial ideology; frescoes; iconography